Carotid Plaque Neovascularization and Hemorrhage Detected by MR Imaging are Associated with Recent Cerebrovascular Ischemic Events - Qiao, Y. (American Society of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: Pathologic studies suggest that neovascularization and hemorrhage are important features of plaque vulnerability for disruption. Our aim was to determine the associations of these features in carotid plaques with previous cerebrovascular ischemic events by using high-resolution CE-MRI. MATERIALS AND METHODS: Forty-seven patients (36 men; mean age 72.5 ± 10 years) underwent CE-MRI and MRA examinations for carotid plaque at 3T. IPH presence was recorded. Neovascularity was categorized by the degree of adventitial enhancement (0, absent; 1, <50%; 2, ≥50%). Reader variability was assessed by using weighted κ. Associations with events were determined by using multivariable logistic regression. RESULTS: Intra- and inter-reader agreement for grading adventitial enhancement were good to excellent. IPH was present in 49% of patients and was associated with events (P = .03). Patients grouped by categories 0, 1, and 2 adventitial enhancement had increasing frequencies of events (14% category 0, 48% category 1, 65% category 2; P = .02). Events were associated with IPH (OR, 10.18; 95% CI, 1.42–72.21) and adventitial enhancement (compared with category 0: OR, 14.90, 95% CI, 0.98–225.93 for category 1; OR, 51.17, 95% CI, 3.4–469.8 for category 2) after controlling for age, sex, cardiovascular risk factors, wall thickness, and stenosis. Stenosis was not associated with events. CONCLUSIONS: Adventitial enhancement and IPH are independently associated with previous events and may provide important insight into stroke risk not achievable by stenosis.